International NGOs' framing of their legitimacy in protecting children's rights - A qualitative content analysis - Dahlstedt,Louise (2020)
The Convention on the Rights of the Child declares how state parties and civil society share responsibility in protecting children’s rights, as non-governmental organisations are intended to intercede when the state’s initiatives are inadequate. In this bachelor thesis the question of how international children’s rights organisations frame their legitimacy for doing the aforementioned is examined. By answering this question, the study’s purpose is achieved through exploring how Save the Children International, Plan International and SOS Children’s Villages International understand their role as complement to the state in protecting children’s rights. The thesis’ purpose is executed through a qualitative content analysis of the organisations’ annual reports from 2018, as well as applying the theoretical concept of political responsibility to reveal what arguments the NGOs use. The results demonstrate that the international child rights organisations perceive themselves as legitimate in their function via established expertise, agenda-setting as well as through relationships. It was concluded that these justifications were all connected to the state and its inability to attain its obligations.
Keywords: Legitimacy; international NGOs; civil society; political responsibility; children’s rights; human rights; state responsibility Legitimitet; internationella icke-statliga organisationer; civilsamhälle; politiskt ansvar; barns rättigheter; mänskliga rättigheter; statligt ansvar